Modern American communes a dictionary - Sutton, Robert P. 1940-2009 (Greenwood Press, 2005)
This reference source contains biographies and historical overviews of 20th-century communes and utopias in the United States and those individuals involved with them. Robert P. Sutton provides a comprehensive history of both religious and secular utopian communities